Travel preferences of the residents of Guimarães: a revised model of push and pull motives - Mendes, Raquel (2013)
The historic center of the Portuguese city of Guimarães is a world heritage site (UNESCO) since 2001, having hosted the European Capital of Culture (ECOC) in 2012. In this sense, Guimarães has made a major effort in promoting tourism, positioning itself as an urban and cultural tourism destination. The present paper has two objectives. The first, to examine if an existing push and pull motivation model finds statistical support with regard to the population of the municipality of Guimarães, a cultural tourism destination. The second, to study the role that important socio-demographic variables, such as gender, age, and education, play in determining travel motivations of residents from this municipality. Insight on tourism motivation may be an important policy tool for tourism planners and managers in the development of products and marketing strategies. The empirical analysis is undertaken based on questionnaires administered in 2012 to residents of Guimarães. The present study shows that gender, age and education make a difference with regard to travel motivations.